Comparison of Chiral Separations of Aminophosphonic Acids and Their Aminocarboxylic Acid Analogs Using a Crown Ether Column. Issue 7 (23rd May 2013) - Barnhart, Wesley W.; Xia, Xiaoyang; Jensen, Randy; Gahm, Kyung H.
ABSTRACT: Crown ethers are capable of complexing with primary amines and have been utilized in chromatography to separate amino acid racemates. This application has been extended to resolve (1‐amino‐1‐phenylmethyl)phosphonic acid and (1‐aminoethyl)phosphonic acid racemates, along with their aminocarboxylic acid analogs (2‐phenylglycine and alanine, respectively), via a ChiroSil RCA crown ether based chiral stationary phase. Effects of the organic modifier, temperature, and acid type and concentration on retention and selectivity were also investigated. Trends in retention and selectivity varied between aminophosponic acids and their aminocarboxylic analogs. Computer modeling and 1 H NMR analyses were performed to potentially gain a better understanding of interactions of the aforementioned molecules with the ChiroSil RCA chiral stationary phase. Theoretical predictions of the most stable conformations for ( R )‐ and ( S )‐enantiomers were compared to elution order; it was found that the elution order agreed with molecular modeling such that the longest retention correlated with the predicted most stable complex between the enantiomer and crown ether. 1 H NMR demonstrated interactions of aminophosphonic and aminocarboxylic racemates with (+)‐(18‐crown‐6)‐2, 3, 11, 12‐tetracarboxylic acid in solution and was utilized to determine enantiomeric excess of (1‐amino‐1‐phenylmethyl)phosphonic acid after its enantioenrichment via crystallization through diastereomeric salt formation with the crown ether followed by filtration. Chirality 25:369–378, 2013 . © 2013 Wiley Periodicals, Inc.